Hubungan Tingkat Stres dengan Derajat Hipertensi pada Pasien Hipertensi di Wilayah Kerja Puskesmas Andalas Padang Tahun 2014 - Muhammad Saleh; Basmanelly; Emil Huriani (Fakultas Keperawatan Universitas Andalas, 2014)
Hypertension is one of the factors causing death the large number of deaths in West Sumatra that increasing in numbered, hypertension is the second causing of death after heart disease, which one of risk factor is stress. This study aims to examine the relationship between levels of stress and degree of hypertension-on-hypertension patients in Andalas Public health center Padang year 2014. This study uses Correlation study design with cross sectional design. Samples in this study amounted to 64 hypertensive patients were taken with accidental sampling method. This research takes time from 18 January until 11 July 2014. Data collection was performed at Andalas Public health center Padang with Depression Anxiety and Stress using Scale (DASS).Univariate data were analyzed with average value of the stress level of 20.69, which minimum value 15 and maximum value 32. Distribution of 1 degree of hypertension frequency (65.6%) and 2 degrees hypertension (34.4%). Bivariate analysis with the Spearman test. The results showed that there is a significant relationship between the level of stress and the degree of hypertension-on-hypertension patients in Andalas Public health center Padang Year 2014. Correlation test results the correlation values (r) stress levels with the degree of hypertension 0.486 with a significance value p= 0.000 (p <0, 05) and the positive direction means if me stress level get higher so the degree of hypertension too. Based on the result suggested to the respondent able to controlling of stress with relaxation techniques and stress management. suggestion to nurses can provide the intervention techniques that can reduce the stress of hypertension patients.